Smart measuring cup / A'qilah Arifah Faisal … [et al.] - FAISAL, A'QILAH ARIFAH; MOHAMMAD, NUR INSYIRAH; ABD RASID, WARDAH ZAHIRAH (2017)
The product to be develop is smart measuring cup. Smart measuring cup is a baking tool that is improvised based on existing product which has the function of measuring and weighing the ingredients as well as detecting and auto-removed the excess ingredients.